Nonlinear evolution of hypersonic waves with Akhiezer damping and their role in coherent bremsstrahlung in crystals - Vodyanitskii, A.A. (Вопросы атомной науки и техники, 2007)
The asymptotic and numerical analysis of the nonlinear hypersonic wave propagation is fulfilled. Some peculiarities of the linear propagation of a periodic signal, such as the formation of a periodic shock wave, have been found. Applications to coherent bremsstrahlung of fast electrons are pointed out. Представлені асимптотичний і чисельний аналізи розповсюдження нелінійних гіперзвукових хвиль. Досліджено формування періодичних нелінійної та ударної хвиль для періодичного граничного сигналу. Вказано на застосування до когерентного гальмівного випромінювання швидких електронів. Представлены асимптотический и численный анализы распространения нелинейных гиперзвуковых волн. Исследовано формирование периодических нелинейной и ударной волн для периодического граничного сигнала. Указаны приложения к когерентному тормозному излучению быстрых электронов.